POLISH REAL ESTATE FUNDS AND INTERNATIONAL EXPERIENCE - Iwona Foryś; Małgorzata Tarczyńska-Łuniewska (Acta Scientiarum Polonorum. Oeconomia, 2017)
Funds investing in the Polish real estate market have been functioning since 2004, but they have lived through both the times of the 2006–2008 boom and the times of the 2009–2014 crisis. The first close-end funds were established in 2004 and were originally intended to close down after eight years. However, their results did not guarantee the return expected by investors. The purpose of the study is to evaluate the performance of the Polish investment funds operating on a young, ten-year-old market in the context of the experience of mature markets with a long history of funds investing in real estate. The paper presents the cause and effect analysis of the impact of macroeconomic factors on the funds’ results as well as of behavioral factors contributing to low interest in the real estate investments with the participation of Polish investment funds operating on the Polish real estate market.